Building a dangerous outpost in the Green Mountain State: A case study of educator preparation policymaking - McGough, David J.; Bedell, Claudine; Tinkler, Barri (Education Policy Analysis Archives, 2018)
Poised at a bifurcation, the educator preparation community in Vermont faced either the adoption of a generic product for the assessment of initial educator licensure candidates or the comprehensive revision of a longstanding state-based assessment portfolio. Using a case study approach and narrative methods, specifically the Narrative Policy Framework (McBeth, Jones, & Shanahan, 2014), the authors analyze a project in which teacher educators intervened to shape the direction of educator preparation policymaking by designing an innovative assessment portfolio and a collaborative calibration system. The analysis reveals insights about the policymaking arena and demonstrates the value of education-related policymaking that includes teacher educators as active agents in collaboration with state personnel and policymakers. The case contributes to the notion of policymaking as a narrative process. In this case, a narrative of hope emerged as a guiding storyline.